Wpływ jednostek zewnętrznych na gospodarkę przedsiębiorstw materiałami - Krzemińska, Danuta (Wydział Prawa i Administracji UAM, 1977)
This paper contains a systematic exposition of external instruments based upon planning, economic turnover and financing rules, that help manage materials in a business. They may take from either of direct orders i.e. decisions imposed by outside decision-makers on the legal regulations basis or, of financial standards i.e. parameters. On the one hand, these instruments restrict business activity and, on the other hand, they provide means for outside decisionmakers to influence enterprise materials management. The state bodies of economic policy set targets which reflect social, nation-wide, objectives. Now, if enterprise decisions to buy or to store materials are to conform with and to realize in practice these targets, it is necessary to exert an influence upon enterprise materials management. The hierarchy of outside units include: — units on the same managerial level as the given enterprise, and — units on other higher levels. The former comprise buyers and sellers linked on the trade agreement basis, whereas the latter consist of units linked on the control basis i.e. superior unit — bank — finance department. In the actual management system an enterprise is bound up both with its trading partner and with superior units, banks and regional state revenue and supervision centres, which means that in managing its materials an enterprise realizes not only its own goals, but also those set by outside units (superior units, banks and finance departments) and by trading partners (buyers and sellers). The managerial system has been evolving from a purely order — based one through the actually existing order — parameter one to a purely (parameter one, where in the last case an enterprise will enjoy its largest freedom in managing materials. A comprehensive analysis of this process must therefore include both vertical and horizontal connections, which jointly influence the policy of purchase and storage of materials in an enterprise.
Outside Units of Material Management in an Enterprise